Review: Diversity of Microorganisms in Global Fermented Foods and Beverages - Tamang, Jyoti P.; Watanabe, Koichi; Holzapfel, Wilhelm H. (Frontiers in Microbiology, 2016)
Majority of global fermented foods is naturally fermented by culturalable and non-culturable microorganisms. Food fermentations represent an extremely valuable cultural heritage in most regions, and harbour a huge genetic potential of valuable but hitherto undiscovered strains. Holistic approaches for identification and complete profiling of both culturalable and non-culturable microorganisms in global fermented foods are interest to food microbiologists. The application of molecular and modern identification tools through culture-independent techniques has thrown new light on the diversity of a number of hitherto unknown and uncultivable microorganisms in naturally fermented foods. Functional bacterial groups (“phylotypes”) may be reflected by their mRNA expression in a particular substrate and not by mere DNA-level detection. An attempt is made here to review the microbiology of some global fermented foods and alcoholic beverages.